Enhancing crop domestication through genomic selection, a case study of intermediate wheatgrass - Crain, Jared; Bajgain, Prabin; Anderson, James; Zhang, Xiaofei; DeHaan, Lee; Poland, Jesse (Dryad, 2019)
Perennial grains could simultaneously provide food for humans and a host
of ecosystem services, including reduced erosion, minimized nitrate
leaching, and increased carbon capture. Yet most of the world’s food and
feed is supplied by annual grains. Efforts to domesticate intermediate
wheatgrass (Thinopyrumn intermedium, IWG) as a perennial grain crop have
been ongoing since the 1980’s. Currently, there are several breeding
programs within North America and Europe working toward developing IWG
into a viable crop. As new breeding efforts are established to provide a
widely adapted crop, questions of how genomic and phenotypic data can be
used among sites and breeding programs have emerged. Utilizing five cycles
of breeding data that span eight years and two breeding programs,
University of Minnesota, St. Paul, MN, and The Land Institute, Salina, KS,
we developed genomic selection (GS) models to predict IWG traits. Seven
traits were evaluated with free-threshing seed, seed mass, and
non-shattering being considered domestication traits while agronomic
traits included spike yield, spikelets per inflorescence, plant height,
and spike length. We used 6,199 genets - unique, heterozygous, individual
plants - that had been profiled with genotyping-by-sequencing, resulting
in 23,495 SNP markers to develop GS models. Within cycles, the predictive
ability of GS was high, ranging from 0.11 to 0.97. Across-cycle
predictions were generally much lower, ranging from -0.22 to 0.76. The
prediction ability for domestication traits was higher than agronomic
traits, with non-shattering and free threshing prediction abilities
ranging from 0.27 to 0.75 whereas spike yield had prediction abilities
ranging from -0.22 to 0.26. These results suggest that progress to reduce
shattering and increase the percent free-threshing grain can be made
irrespective of the location and breeding program. While site-specific
programs may be required for agronomic traits, synergies can be achieved
in rapidly improving key domestication traits for IWG. As other species
are targeted for domestication, these results will aid in rapidly
domesticating new crops.
Data set was collected over eight years 2011-2019 from two different
intermediate wheatgrass (IWG, Thinopyrum intermedium) breeding programs at
The Land Institute, Salina KS, and the University of Minnesota, St. Paul,
MN.  Genotyping-by-sequencing was used for genomic
profiling.
Readme file indicates data scripts and file structures in the zipped data file.
Keywords: GBS (genotyping-by-sequencing); Genomic selection; Thinopyrum intermedium; Principal Component Analysis (PCA); single nucleotide polymorphism SNP; The Land Institute; quantitative trait loci (QTL); perennial crop; crop domestication; shared data resources; multi-environment